1991
DOI: 10.1080/15287399109531570
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxicosis alters avian renal function, calcium, and vitamin d metabolism

Abstract: Experiments were designed to determine the effects of aflatoxicosis on avian renal function, calcium (CA), inorganic phosphorous (Pi), and vitamin D metabolism, and to determine if the effects of aflatoxin are reversible upon discontinuation of toxin administration. Three-week-old male broiler chickens (n = 12 per treatment) received aflatoxin (AF; 2 mg/kg po) or an equal volume of corn oil, the AF carrier vehicle, for 10 consecutive days. After 10 d of treatment, half of the birds from each treatment group we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 26 publications
8
31
0
1
Order By: Relevance
“…The decreased serum total protein, albumin, total cholesterol, triglyceride and glucose values and increased ASAT activity observed in the present study (P < 0.05; Tables 3 and 4) were due to the hepatotoxic effects of AF characterized by the inhibition of protein synthesis and impairment of carbohydrate and lipid metabolism (Rosa et al, 2001). The decrease in serum inorganic phosphorus and creatinine values (P < 0.05) may be related to the nephrotoxic effects of AF in agreement with other studies (Glahn et al, 1991;Harvey et al, 1993).…”
Section: Discussionsupporting
confidence: 81%
“…The decreased serum total protein, albumin, total cholesterol, triglyceride and glucose values and increased ASAT activity observed in the present study (P < 0.05; Tables 3 and 4) were due to the hepatotoxic effects of AF characterized by the inhibition of protein synthesis and impairment of carbohydrate and lipid metabolism (Rosa et al, 2001). The decrease in serum inorganic phosphorus and creatinine values (P < 0.05) may be related to the nephrotoxic effects of AF in agreement with other studies (Glahn et al, 1991;Harvey et al, 1993).…”
Section: Discussionsupporting
confidence: 81%
“…A renal lesion was observed during the intoxication period, where calcium and phosphorus may have been lost. Glahn et al (1991) found that aflatoxin in broiler chickens caused a severe renal lesion which affected calcium and phosphorus metabolism. Serum calcium and phosphorus increased rapidly after the intoxication period.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Glahn et al (1991) observed lower total plasma calcium levels and higher fractional calcium excretion in AF-fed broilers compared with the controls, and concluded the direct and indirect effects of AF on calcium and phosphorus metabolism may due a reduction in the endogenous synthesis of the parathyroid hormone (PTH) and of the renal sensitivity to PTH (Glahn et al, 1991). The supplementation of 2.5 ppm AF (Giroir et al, 1991) or 3.5 ppm AF (Smith et al, 1992) to broiler chicks for three weeks decreased serum calcium and phosphorus levels.…”
Section: Multi-criteria Analysis To Prioritize Energy Sources For Ambmentioning
confidence: 99%
“…The consumption of OTA-contaminated diets (2 mg/kg PO) by three-week-old male broiler chickens for ten days reduced urinary fractional sodium content and potassium excretion (Glahn et al, 1991). On the other hand, Glahn et al (1991) observed lower total plasma calcium levels and higher fractional calcium excretion in AF-fed broilers compared with the controls, and concluded the direct and indirect effects of AF on calcium and phosphorus metabolism may due a reduction in the endogenous synthesis of the parathyroid hormone (PTH) and of the renal sensitivity to PTH (Glahn et al, 1991).…”
Section: Multi-criteria Analysis To Prioritize Energy Sources For Ambmentioning
confidence: 99%